2017
DOI: 10.1080/13880209.2017.1333127
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of hyperglycaemia and modulation of antioxidant status by Alcea rosea seeds in alloxan-induced diabetic rats

Abstract: Context:Alcea rosea L. (Malvaceae) has various medicinal uses including anticancer, anti-inflammatory and analgesic properties. However, there is no report on its antidiabetic activity.Objective:Alcea rosea seed extracts were evaluated for antihyperglycaemic and antioxidative potential in diabetic rats.Materials and methods: Single intra-peritoneal injection of alloxan (130 mg/kg b.w.) was used for induction of diabetes in Albino Wistar rats. Antihyperglycaemic and antioxidant activities of methanol and aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Increased levels of CAT, GSH and SOD against ROS produced by Alloxan induction is owing to the presence of large amounts of antioxidants such as tocopherols, phenolic compounds, and flavonoids, specifically quercetin, kaempferol and chlorogenic acid in MO seed oil that have scavenging potential against ROS. It was also found that Alloxan induction in group II rats markedly increased hepatic MDA levels, which is indicative of increased oxidative stress: these findings correlate with the previous studies 36 . Group treated with the Alloxan+MO seed oil showed significantly lower MDA levels than the Alloxan treated diabetic group (Table 5).…”
Section: Discussionsupporting
confidence: 89%
“…Increased levels of CAT, GSH and SOD against ROS produced by Alloxan induction is owing to the presence of large amounts of antioxidants such as tocopherols, phenolic compounds, and flavonoids, specifically quercetin, kaempferol and chlorogenic acid in MO seed oil that have scavenging potential against ROS. It was also found that Alloxan induction in group II rats markedly increased hepatic MDA levels, which is indicative of increased oxidative stress: these findings correlate with the previous studies 36 . Group treated with the Alloxan+MO seed oil showed significantly lower MDA levels than the Alloxan treated diabetic group (Table 5).…”
Section: Discussionsupporting
confidence: 89%
“…Following the 15 th and 30 th days of treating groups with additives, blood sugar was nonsignificantly lower in A.kurdica (T3) group than that of (T1), (T1), (T0+), and (T0-), respectively. The anti-diabetic activity of Alcea genus was previously shown in alloxan-induced diabetic rates 26 . The hypoglycemic effect of A.kurdica can be linked with their antioxidant activity and phenolic contents that have been reported by Dar et al 27 (Table 1).…”
Section: Resultsmentioning
confidence: 83%
“…Browning is proposed to be due to oxidative stress following high-temperature exposure. A.rosea possess high total phenolic content 26 , and oxidation of phenolic compounds possibly will result in a deep brown color of the mucilage. Furthermore, extraction temperature-induced browning in the color of the polysaccharide/mucilage.…”
Section: Resultsmentioning
confidence: 99%